WWOX, the common fragile site FRA16D gene product, regulates ATM activation and the DNA damage response - Abu-Odeh, Mohammad; Salah, Zaidoun; Herbel, Christoph; Hofmann, Thomas G.; Aqeilan, Rami I. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Genomic instability is a hallmark of cancer. The WW domain-containing oxidoreductase (WWOX) is a tumor suppressor spanning the common chromosomal fragile site FRA16D. Here, we report a direct role of WWOX in DNA damage response (DDR) and DNA repair. We show that Wwox deficiency results in reduced activation of the ataxia telangiectasia-mutated (ATM) checkpoint kinase, inefficient induction and maintenance of γ-H2AX foci, and impaired DNA repair. Mechanistically, we show that, upon DNA damage, WWOX accumulates in the cell nucleus, where it interacts with ATM and enhances its activation. Nuclear accumulation of WWOX is regulated by its K63-linked ubiquitination at lysine residue 274, which is mediated by the E3 ubiquitin ligase ITCH. These findings identify a novel role for the tumor suppressor WWOX and show that loss of WWOX expression may drive genomic instability and provide an advantage for clonal expansion of neoplastic cells.
Gesehen am 01.12.2020